DESIGN OF SUTI WATER SYSTEM INVENTORY APPLICATION USING THE USER-CENTERED DESIGN (UCD) METHOD - Farhan, Muhammad; Fajri, Hersanto; Wulandari, Berlina; Nur, Muh. Arbiyansyah (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2025)
Inventory management (stock) is an important factor for business operational continuity. The Suti Water bottled water business unit, managed by the Indonesian Islamic Boarding School Cooperation Agency (BKsPPI), was facing serious constraints where the manual recording system often resulted in delays and data inaccuracies, which had a significant impact on operational efficiency. This study aimed to overcome these challenges by designing and developing an inventory application prototype with a focus on optimizing the User Interface (UI) and User Experience (UX). The User-Centered Design (UCD) methodology was adopted to ensure that the application design was centered on the real needs of the Suti Water Main Distributor warehouse staff. Following development, the application's usability was evaluated using the System Usability Scale (SUS). The testing results showed a SUS score of 93.0, which placed the application in the 'Acceptable' category with an "Excellent" rating. These findings demonstrate that the developed prototype is an effective and highly accepted solution by the users. Furthermore, the application proved to reduce transaction recording time and significantly minimize data errors..